2013
DOI: 10.1186/1472-6785-13-34
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced primers for amplification of DNA barcodes from a broad range of marine metazoans

Abstract: BackgroundBuilding reference libraries of DNA barcodes is relatively straightforward when specifically designed primers are available to amplify the COI-5P region from a relatively narrow taxonomic group (e.g. single class or single order). DNA barcoding marine communities have been comparatively harder to accomplish due to the broad taxonomic diversity and lack of consistently efficient primers. Although some of the so-called “universal” primers have been relatively successful, they still fail to amplify COI-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
114
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(117 citation statements)
references
References 35 publications
1
114
0
2
Order By: Relevance
“…To rule out the possibility of a New Zealand incursion of O. edulis and, therefore with it, an incidental incursion of B. ostreae, the species of the oyster host was identified by DNA barcoding. The 4 DNA templates described above in the Bonamia-genus PCR assay had their respective cytochrome oxidase 1 (cox1) gene DNA barcoded using the Lobo et al (2013) conventional PCR assay. The forward primer Lobo-F1 (5'-KBT CHA CAA AYC AYA ARG AYA THG G-3') was paired with the reverse primer Lobo-R1 (5-TAA ACY TCW GGR TGW CCR AAR AAY CA-3') to produce an expected amplicon of 708 bp.…”
Section: In Situ Hybridisationmentioning
confidence: 99%
“…To rule out the possibility of a New Zealand incursion of O. edulis and, therefore with it, an incidental incursion of B. ostreae, the species of the oyster host was identified by DNA barcoding. The 4 DNA templates described above in the Bonamia-genus PCR assay had their respective cytochrome oxidase 1 (cox1) gene DNA barcoded using the Lobo et al (2013) conventional PCR assay. The forward primer Lobo-F1 (5'-KBT CHA CAA AYC AYA ARG AYA THG G-3') was paired with the reverse primer Lobo-R1 (5-TAA ACY TCW GGR TGW CCR AAR AAY CA-3') to produce an expected amplicon of 708 bp.…”
Section: In Situ Hybridisationmentioning
confidence: 99%
“…The intraspecific distances obtained for our specimens were 0.3 to 0.7%. Many studies have been carried out using the mitochondrial DNA sequences of the COI-5P, which have confirmed that DNA barcodes (Hebert et al 2003) are a reliable tool to discriminate species of crustaceans (Lobo et al 2013(Lobo et al , 2016, including cirripedes (Chan et al 2009). Ratnasingham & Hebert (2013) suggested that 2.2% of average intraspecific distance is a reference threshold for within-species boundaries, which is quite far from the divergences found in this study.…”
Section: Discussionmentioning
confidence: 97%
“…Three mitochondrial genetic markers (the barcode region of the cytochrome c oxidase subunit I (COI-5P), 12S and 16S) were amplified in a Techne TC-PLUS thermal cycler (VWR International, LLC, Radnor, USA). For the COI-5P, the Go Taq ® G2 colorless master mix (Promega) and the primer pair LoboF1 (5'-KBTCHACAAAYCAYAARGAYATHGG-3') and LoboR1 (5'-TAAACYTCWGGRTGWCCRAARAAYCA-3') (Lobo et al 2013) were used. The PCR thermal cycling conditions were as follows: 1) 94 °C (5'); 2) 5 cycles: 94 °C (30''), 45 °C (1'30''), 72 °C (1'); 3) 45 cycles: 94 °C (30''), 54 °C (1'30''), 72 °C (1'); 4) 72 °C (5').…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have been reported that sequence diversity in a ~650 bp region near the 5' end of the MT-COI gene provides strong species-level resolution for varied animal groups, including birds [1,12], fishes [7,30], springtails [5,24], spiders [5,6] and moths [16,20]. It has been reported that the primer pair, (LCO_MT1_NC101214 and LCO_MT2_NC021214) was not so ''universal'' as thought before, as it would still fail to amplify some taxa [21,28]. While performing BLAST (using BLASTn and BLASTx), the sequences of the above said species showed varied degrees of similarity with existing data in the NCBI database (Table 1).…”
Section: Parapenaeopsis Sculptillismentioning
confidence: 99%